2020
DOI: 10.1017/aog.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

Radio-echo soundings on Icelandic temperate glaciers: history of techniques and findings

Abstract: Since the mid-1970s radio-echo soundings have been conducted on Iceland's temperate glaciers. Since then, low-frequency radar technology has furthered the study of most of the island's ice caps. Their masses and volumes have been quantified and detailed subglacial topographic maps produced which demarcate glacial drainage basins and identify subglacial lakes and volcanoes. Even internal tephra layers have been charted. The resulting data have been used to force and validate models of past and future glacier ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 54 publications
(42 reference statements)
0
30
0
Order By: Relevance
“…Other early surveys were also led by Russia, Germany, Iceland, Italy, China, and Canada (among others) across Antarctica and Greenland, as well as Iceland, Arctic Ice Caps, and mountain glaciers (e.g. Drewry, 1983; Bingham and Siegert, 2007; Björnsson, 2020; Popov, 2020). Planetary radar sounders have also been used, or are planned, to observe the subsurface and near-surface conditions of Mars, Earth's moon, comets and the icy moons of Jupiter (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other early surveys were also led by Russia, Germany, Iceland, Italy, China, and Canada (among others) across Antarctica and Greenland, as well as Iceland, Arctic Ice Caps, and mountain glaciers (e.g. Drewry, 1983; Bingham and Siegert, 2007; Björnsson, 2020; Popov, 2020). Planetary radar sounders have also been used, or are planned, to observe the subsurface and near-surface conditions of Mars, Earth's moon, comets and the icy moons of Jupiter (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of a glacier can be obtained by integrating the ice thickness, calculated as the difference between surface and bedrock DEMs. Bedrock DEMs for the three largest ice caps have been made from dense radio-echo sounding data (Björnsson and Pálsson, 2020) and are assumed stable over time. Their volumes have been calculated using the following surface DEMs: lidar surface DEM of Hofsjökull from 2008 (Jóhannesson et al, 2013), a SPOT5-HRS (Korona et al, 2009) surface DEM of Vatnajökull from 2010, and a SPOT5 surface DEM of Langjökull from 2004 (Korona et al, 2009;Pálsson et al, 2012).…”
Section: Volume-area Scalingmentioning
confidence: 99%
“…The surface and bedrock topographies of the largest ice caps have been measured in radio-echo sounding campaigns carried out since 1977. Radioecho sounding on the temperate ice caps in Iceland required a much longer electromagnetic wavelength than had been used on the cold polar ice caps (Björnsson and Pálsson, 2020). The pioneering measurements resulted in a good knowledge of the subglacial topography of the ice caps and their total volume FIGURE 1 | Map of Iceland showing the glaciers considered in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis favors center frequencies ≤ ~10 MHz to keep the signal-to-noise ratio high between the ice-bed reflection (signal) and the volume scattering arising from the cavities (noise). Their lucid description of this challenge motivated the development of numerous "low-frequency" radar sounders (e.g., Watts and Wright, 1981;Fountain and Jacobel, 1997;Conway et al, 2009;Mingo and Flowers, 2010;Rignot et al, 2013;Arnold et al, 2018;Björnsson and Pálsson, 2020). However, subsequent advances in available hardware, system design and processing demonstrated that higher-frequency (> 10 MHz) radar sounders can also sound hundreds of meters of temperate ice (e.g., Rutishauser et al, 2016;Pritchard et al, 2020).…”
Section: Introductionmentioning
confidence: 99%